The second survey of the Saudi Acute Myocardial Infarction Registry Program: Main results and temporal changes in care (STARS-2 program) - Ayman AlSaleh; Shukri M. AlSaif; Osama Alhadramy; Mohammed Alshehri; Khalid Al Faraidy; Fawaz Almutairi; Abdulhalim J. Kinsara; Mushabab Al-Murayeh; Abdullah E. Ghabashi; Mirvat Alasnag; Gamal Abdin Hussein; Tamer M. Askar; et al. (PLoS ONE, 2025)
Background The Saudi Acute Myocardial Infarction Registry (STARS) program aims to evaluate the clinical characteristics, management, and outcomes of a representative sample of patients with acute myocardial infarction (AMI) in Saudi Arabia. This second phase evaluates temporal changes in patient care, demographics, and the management benchmarks for AMI. Methods and findings We created a 5-year recurring, multi-center prospective registry that utilizes a snapshot design in 50 hospitals from various healthcare sectors in Saudi Arabia. The study’s recruitment phase spanned from September 3, 2021, to January 6, 2023. During these 16 months, 2,690 patients presenting with acute myocardial infarction (AMI) with or without ST-segment elevation (STEMI or NSTEMI, respectively) were enrolled. The mean age (± SD) of the overall population was 57 (±12.4) years, 70% were Saudi citizens, 82% were men, and (48.8%) of the total patients had STEMI. Fifty-eight percent of patients had diabetes mellitus and 58% had hypertension. Of the total population with STEMI, primary percutaneous coronary intervention (PCI) was performed in 619 patients (47.1%), thrombolytics were given to 584 patients (44.5%), and 110 patients had no reperfusion (8.4%). Among patients who presented within 24 h of symptom onset, the door-to-balloon (DTB) time was 63 min (IQR: 43), with 75.6% achieving DTB < 90 min, whereas the door-to-needle (DTN) was 25 min (IQR: 34), with 57% achieving DTN < 60 min. Thirty-nine percent of patients failed lytic reperfusion and 96% of these required rescue PCI. In 52% of instances, the failure to receive reperfusion therapy was attributed to patients’ late presentation. At presentation, only 8.5% of cases were transferred by the Emergency Medical Services. Approximately one-fourth of patients with NSTEMI did not undergo a coronary angiogram. All-cause mortality was 2.4% with no significant difference between sexes or nationalities. Conclusion This nationwide AMI registry revealed younger age at presentation with a high prevalence of risk factors for coronary artery disease. While primary PCI key performance indicators have improved from the previous phase, further progress is needed in EMS utilization and acute revascularization for STEMI and NSTEMI.